2002
DOI: 10.1097/00003246-200206000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide synthase pathway in the central nervous system and vasopressin release during experimental septic shock*

Abstract: These data indicate that central nitric oxide arising from the inducible nitric oxide synthase pathway plays an important inhibitory role in vasopressin release during experimental septic shock and may be responsible for the hypotension occurring in this vasodilatory shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
0
27

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 25 publications
7
48
0
27
Order By: Relevance
“…Vasopressin was administered, however, also for a second reason. Thus, in the early phase of septic shock a reflex increase in vasopressin is found (Tarpey et al, 1998;Landry & Oliver, 2001;Giusti-Paiva et al, 2002), which, however, cannot occur in pithed animals since reflex loops involving the brain are destroyed. The possibility that vasopressin acted via a presynaptic site had to be considered.…”
Section: G Godlewski Et Almentioning
confidence: 99%
“…Vasopressin was administered, however, also for a second reason. Thus, in the early phase of septic shock a reflex increase in vasopressin is found (Tarpey et al, 1998;Landry & Oliver, 2001;Giusti-Paiva et al, 2002), which, however, cannot occur in pithed animals since reflex loops involving the brain are destroyed. The possibility that vasopressin acted via a presynaptic site had to be considered.…”
Section: G Godlewski Et Almentioning
confidence: 99%
“…Hence, we will refer to this response as anapyrexia. Of interest is the fact that LPS-induced anapyrexia usually occurs alongside with hypotensive shock (4,13,63,114,189,200,262,285), an observation that raises the question as to whether hypoxia associated with LPS shock is the trigger of the fever-anapyrexia switch. This question has not yet been answered, though a study involving cyclooxygenase inhibition points to a possible disconnect between the anapyrexic and hypotensive responses to a high LPS dose (338).…”
Section: Regulated Changes In T B : Fever and Anapyrexiamentioning
confidence: 99%
“…Following these procedures, rats were immediately decapitated for collection of blood. The doses of LPS and L-NAME and the time interval between the drugs were chosen on the basis of previous studies [2,8,32] and because pilot experiments indicated that this protocol lead to the most consistent and repeatable results.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…Moreover, it has been demonstrated that NO mediates physiological responses in the central nervous system (CNS), immune system and endocrine system [13]. It has also been demonstrated that NO may act as a modulator of vasopressin (AVP) release/synthesis in normal [18,35] and septic rats [8]. AVP plays an important role in the regulation of arterial blood pressure and osmolarity.…”
Section: Introductionmentioning
confidence: 99%